Modes of land control in transfrontier conservation areas : a case of green grabbing - Thakholi, Lerato (Department of Environmental and Geographical Science, 2016)
In light of the current literature on green grabbing, this study is motivated by the need to understand whether TFCAs are characterized by green grabbing and what form they take if indeed they are unfolding there. It investigated the modes of land control and transfer - within the Lesotho component of the Maloti Drakensberg Transfrontier Conservation Area and South Africa's Greater Mapungubwe Transfrontier Conservation Area - in order to explore the politics of land in TFCAs through the green grabbing lens. Global environmental organizations are increasingly calling for more terrestrial and marine resources to be protected from the looming global environmental crisis. The knowledge production about environmental problems, threats and solutions are often articulated at the global level through reports and conventions and are expected to be adopted at the local level. One such solution to loss of biodiversity that has enjoyed increasing support in southern Africa is the concept of the Peace Parks in the form of Transfrontier Conservation Areas. With the land question an ever brooding cloud over southern Africa, this study finds itself interrogating TFCAs and the land questions they raise. Taking into consideration the current land claims in South Africa, the contested issue of traditional authorities and the problems associated with communal land tenure. The study used hegemony as a lens through which to understand how conservation initiatives at the local level are an amalgamation of how the global environmental bloc has conceptualized conservation both as a practice and an idea. One such idea that has been widely popularised is the need for more land for conservation purposes. This approach allowed the identification of environmental international conventions and protocols as a first step in a series of prongs that legitimizes green grabbing. Furthermore, it used property rights to explore how legal green grabbing occur, that is, how property rights are used by private land owners as well as the state to appropriate more land, and in some instances how property rights were used to resist the encroachment of conservation in the frontier.